Kualitas Kertas Seni Berbahan Baku Pelepah Tanaman Salak Dengan Perlakuan Konsentrasi Naoh Dan Konsentrasi Lem Pvac - Widyawati, Anis; , Triastuti Rahayu, S.Si., M.SI (2016)
The salacca midrib has not been used and just be a waste whereas content of 42.54% high cellulose which can be used to make art paper. This research aims to determine the quality of the salacca midrib (tensile strength, tear strength, and sensory) by NaOH treatment concentration and concentration of PVAc. This research used an experimental method completely randomized design (CRD) two factorial. Factor 1: The concentration of NaOH (K), K0 = Without concentration of NaOH, K1 = 10%, K2 = 15%. Factor 2: Concentration of PVAc (T), T1 = 2%, T2 = 5%. Test results average tensile strength highest in treatment K1T2 (concentration of NaOH 10% and concentration of PVAC 5% ) 0,535 N / mm2, the average tear strength highest in treatment K1T2 (concentration of NaOH 10% and concentration of PVAC 5% ) 23.972 N. The test results of sensory properties of the highest in treatment K0T1 texture (without NaOH concentration and concentration PVAc 2%), Appearance of the highest fiber contained in two treatments, that is K0T1 treatment (without NaOH concentration, concentration of glue 2%) and treatment K0T2 (without NaOH concentration, concentration PVAC 5%), and art paper most favored by public in treatment K2T1 (concentration of NaOH 15% and concentration of PVAc 2%.